Extraction of some heavy metals using ionic liquid systems - Kitagawa, Akiharu (2018)
Since the rise of industrialization, discharging of industrial wastewater containing heavy metals, such as from mining, agricultural plants, electronic waste, and pharmaceutical industries, has raised serious concerns due to their high toxicities to environment and the human body. Further, metal-containing wastewater treatments are generally complicated, costly, and energy intensive. To combat such issues, ionic liquids have been investigated to simplify the wastewater treatment processes. The previous studies have shown potential uses of ionic liquids in separation of metal ions from aqueous solutions by means of a biphasic system. In this project, ionic liquids with quaternary triethylammonium cation and bis(trifluoromethylsulfonyl)amide anion were synthesized and compared to extract Co(II), Cu(II), Pb(II), and Hg(II) from aqueous phase. Two groups of ionic liquids containing alkane or ethylene glycol functional group were studied. To further enhance the extraction efficiency, 2-thenoyltrifluoroacetone was added to the ionic liquid systems. The outcome of the extractions and interaction of water, ionic liquids, and 2-thenoyltrifluoroacetone were analysed by ICP-OES, UV-vis spectroscopy, TGA analysis, and ATR-FTIR spectroscopy.